2004
DOI: 10.1017/s0266462304001059
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the NHS Economic Evaluation Database to researchers undertaking technology assessment reviews

Abstract: NHS EED is a useful tool for a variety of tasks in the NICE/TAR process but not, unsurprisingly, as a replacement for understanding primary studies. There is, however, a need to reduce the impact of time lags between the publication of economic evaluations and the appearance of abstracts relating to them on NHS EED. The results will inform future developments of the NHS EED database, which should increase its usefulness to researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The aim of NHS EED was to bring together and quality appraise economic evaluations that were spread across many databases and paper resources. The database received coverage in the BMJ and research showed that it was valued by its users (Nixon et al, ; Nixon et al, ). DARE performed a similar role for systematic reviews.…”
mentioning
confidence: 99%
“…The aim of NHS EED was to bring together and quality appraise economic evaluations that were spread across many databases and paper resources. The database received coverage in the BMJ and research showed that it was valued by its users (Nixon et al, ; Nixon et al, ). DARE performed a similar role for systematic reviews.…”
mentioning
confidence: 99%
“…However, some of the concerns raised by decision makers could be addressed by changes in the ways economic evaluations are accessed and presented. Several studies have indicated that databases such as NHS EED may need to be further developed and adapted to tailor abstract records more closely to users' needs (11;14;15).…”
mentioning
confidence: 99%